Fiscal policy and the 'Great Recession' in the euro area - Günter Coenen; Roland Straub; Mathias Trabandt (European Central Bank (ECB), 2012)
How much did fiscal policy contribute to euro area real GDP growth during the Great Recession? We estimate that discretionary fiscal measures have increased annualized quarterly real GDP growth during the crisis by up to 1.6 percentage points. We obtain our result by using an extended version of the European Central Bank's New Area-Wide Model with a rich specification of the fiscal sector. A detailed modeling of the fiscal sector and the incorporation of as many as eight fiscal time series appear pivotal for our result.
Keywords: C11; E32; E62; 330; Bayesian inference; DSGE modelling; euro area